Rwanda : Detailed Assessment Report-Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2015)
This paper discusses key findings and recommendations of the Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism (AML/CFT) for Rwanda. Rwanda has taken considerable steps over the last years to establish a national AML/CFT framework. The Rwandan authorities have made great progress in modernizing the financial sector, and aim at making it more attractive to foreign investors. Although the risks of money laundering and terrorist financing do not appear to be particularly significant in Rwanda, further action should be taken to bolster the legal framework, improve its implementation, strengthen overall supervision of reporting entities within the financial sector, and mitigate the potential domestic and cross-border risks.